Too Cold to Sink: The Irony of Survival in "Life is Fine" Using Formalism - Katuwal, Gita (Rupantaran: A Multidisciplinary Journal, 2026)
This paper explores Langston Hughes’s poem "Life is Fine" from a formalist perspective, focusing on how the poem’s structural, linguistic, and literary features create a big irony about the survival of life and resilience. Through close evaluation of Hughes’s use of rhyme, repetition, imagery, and tone, the study demonstrates how the poem contrasts the speaker’s despair and attempts to end his life with an ultimate affirmation to live the life. The poem’s rhythmic patterns create a controlled, almost musical quality that contrasts with the dark subject matter, producing a tension that focuses on the complexity of human emotions. The repetition of key phrases motivates a shift in mood from hopelessness to a resigned acceptance. This synergy of form and content shows that the poem’s irony is not just thematic but deeply integrated into its formal elements. Finally, the analysis explores how "Life is Fine" depicts survival not as mere fortitude, but as an ironic, multifaceted experience shaped by suffering and hope.